# Write the quadratic equation in standard form and then choose the value of "b." (2x - 1)(x + 5) = 0

We will use the concept of the general form of quadratic equation in order to find the value of b.

### Answer: 2x^{2} + 9x - 5 = 0 is in its general form with a = 2, b = 9, c = -5. Thus, the value of b is 9.

Let us see how we will use the concept of the general form of quadratic equation in order to find the value of b.

**Explanation**:

The general form of a quadratic equation is given by ax^{2} + bx + c = 0.

We have been given equation in the form of (2x - 1)(x + 5) = 0

On solving we get, 2x^{2} + 9x - 5 = 0

If we compare 2x^{2} + 9x - 5 = 0 with the general form of quadratic equation that is ax^{2} + bx + c = 0

We can say that 2x^{2} + 9x - 5 = 0 is in its general form with a = 2, b = 9, c = -5